Last visit was: 21 Jun 2024, 01:20 It is currently 21 Jun 2024, 01:20
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
User avatar
Manager
Manager
Joined: 09 Feb 2013
Posts: 104
Own Kudos [?]: 4125 [97]
Given Kudos: 17
Send PM
Most Helpful Reply
Math Expert
Joined: 02 Sep 2009
Posts: 93895
Own Kudos [?]: 633521 [27]
Given Kudos: 82410
Send PM
User avatar
Manager
Manager
Joined: 03 Jun 2013
Status:Training
Posts: 69
Own Kudos [?]: 569 [5]
Given Kudos: 3
Location: Canada
GPA: 3.7
Send PM
General Discussion
avatar
Intern
Intern
Joined: 17 Oct 2012
Posts: 13
Own Kudos [?]: 4 [1]
Given Kudos: 1
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
1
Kudos
b(a-c)=0 => b=0 or a=c

You can see B in an easier way:
Inequalities hold when we raise them to power on both sides. so a^2= c^2. => b.a^2= b.c^2. Thus B follows right away.

I agree with other explainations by Bunuel.
User avatar
Intern
Intern
Joined: 05 Mar 2013
Posts: 13
Own Kudos [?]: 6 [0]
Given Kudos: 5
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Bunuel wrote:
emmak wrote:
For integers a, b, and c, if ab = bc, then which of the following must also be true?

A. a = c
B. a^2*b=b*c^2
C. a/c = 1
D. abc > bc
E. a + b + c = 0


\(ab = bc\) --> \(ab-bc=0\) --> \(b(a-c)=0\)--> \(b=0\) or \(a=c\).


B. a^2*b=b*c^2 --> \(b(a^2-c^2)=0\) --> \(b(a-c)(a+c)=0\). Now, since \(b=0\) or \(a=c\), then \(b(a-c)(a+c)\) does equal to zero. So, we have that this options must be true.

Answer: B.



for answer choice B, could you also say that if a = -c it also equals zero?

Also, why do all of the possible answers equaling zero in choice B mean that B must be true?
User avatar
Intern
Intern
Joined: 05 Mar 2013
Posts: 13
Own Kudos [?]: 6 [0]
Given Kudos: 5
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
i'm still a little confused by the answer choices.

is it because the question stem equates to B=0 OR A=C

so for answer choice A, A doesnt have to equal C because the B equaling 0 will just make the whole expression 0

but then for answer choice B, since B=0 OR A=C, since 1 or the 3 groups in parentheses will be 0, it will make the whole expression 0, therefore B must be true?
User avatar
Director
Director
Joined: 02 Sep 2012
Status:Far, far away!
Posts: 857
Own Kudos [?]: 4911 [0]
Given Kudos: 219
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
dhlee922 wrote:
i'm still a little confused by the answer choices.

is it because the question stem equates to B=0 OR A=C

so for answer choice A, A doesnt have to equal C because the B equaling 0 will just make the whole expression 0

but then for answer choice B, since B=0 OR A=C, since 1 or the 3 groups in parentheses will be 0, it will make the whole expression 0, therefore B must be true?



Yes, exactly. We know that or b=0 or a-c=0 ( or both) .

We can rewrite B as \(b(a-c)(a+c)\), and since at least one of the terms is 0, the whole expression is 0.
Math Expert
Joined: 02 Sep 2009
Posts: 93895
Own Kudos [?]: 633521 [0]
Given Kudos: 82410
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Expert Reply
dhlee922 wrote:
i'm still a little confused by the answer choices.

is it because the question stem equates to B=0 OR A=C

so for answer choice A, A doesnt have to equal C because the B equaling 0 will just make the whole expression 0

but then for answer choice B, since B=0 OR A=C, since 1 or the 3 groups in parentheses will be 0, it will make the whole expression 0, therefore B must be true?


Yes, for A, if b=0, then a may or may not equal to c.

As for B, since b=0 or a=c (a-c=0), then b(a-c)(a+c)=0 must be true, since either the first or the second multiple (or both) is 0.

Hope it's clear.
User avatar
Intern
Intern
Joined: 05 Mar 2013
Posts: 13
Own Kudos [?]: 6 [0]
Given Kudos: 5
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
yes, thank you everyone for your replies! geez, i find this one to be pretty tricky, but it's only 600-700 level, ugh
Intern
Intern
Joined: 26 Jan 2018
Posts: 3
Own Kudos [?]: 0 [0]
Given Kudos: 0
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Hi everyone,

This question is messing with everything I know (which is good). Isn't it legal to divide both parts of the equation by the same value? In this case, by b:

ab = bc --> (ab)/b = (bc)/b --> a = c

What am I doing wrong here?

Thanks!
VP
VP
Joined: 14 Feb 2017
Posts: 1107
Own Kudos [?]: 2177 [0]
Given Kudos: 368
Location: Australia
Concentration: Technology, Strategy
GMAT 1: 560 Q41 V26
GMAT 2: 550 Q43 V23
GMAT 3: 650 Q47 V33
GMAT 4: 650 Q44 V36
GMAT 5: 600 Q38 V35
GMAT 6: 710 Q47 V41
WE:Management Consulting (Consulting)
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Official Explanation:
Correct Answer: B

Choices A and C are essentially identical, and should be regarded with suspicion. Upon further review, if b were to equal 0, then a need not necessarily equal b. Try numbers: a = 1, b = 0, c = 2, then (1)(0) = (0)(2), but 1 does not equal 2. Because b could equal zero, answer choice D is also incorrect, as the two sides of the inequality would both equal zero, and therefore be equal. Answer choice E is also not necessarily true, as demonstrated by the trial numbers above. Answer choice B is correct, as it is true both if a = c, or if b is equal to zero.
Intern
Intern
Joined: 07 May 2019
Posts: 6
Own Kudos [?]: 3 [0]
Given Kudos: 542
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
mattce wrote:
dhlee922 wrote:
Bunuel wrote:

\(ab = bc\) --> \(ab-bc=0\) --> \(b(a-c)=0\)--> \(b=0\) or \(a=c\).

B. a^2*b=b*c^2 --> \(b(a^2-c^2)=0\) --> \(b(a-c)(a+c)=0\). Now, since \(b=0\) or \(a=c\), then \(b(a-c)(a+c)\) does equal to zero. So, we have that this options must be true.

Answer: B.


for answer choice B, could you also say that if a = -c it also equals zero?


The point here is that analyzing the initial equation ab = bc, we know that either b = 0 or a = c.
Plugging in either of these values results in b(a-c)(a+c) being equal to zero.
I think you're confusion comes from extracting "a = -c" from "b(a-c)(a+c) = 0" as opposed to extracting information from the original equation ab = bc (which is what we need to do).

dhlee922 wrote:
Also, why do all of the possible answers equaling zero in choice B mean that B must be true?


Continuing from above:
So recall that from the first equation, b = 0 or a = c.
The expanded term b(a-c)(a+c) is an alternate expression for the second option; i.e, the fact that both of the possible necessary truths (b = 0; a = c) lead to b(a-c)(a+c) = 0 means that the equivalent expression, a^2 * b = b * c^2 must also be true.

I hope that's clear!


Clarity did not come to me from this thread until I read your explanation, and I'm very grateful that you took the time to post it.
Intern
Intern
Joined: 16 Jun 2019
Posts: 2
Own Kudos [?]: 0 [0]
Given Kudos: 0
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Hi Bunuel- how come we can't start out by dividing both sides by b? I dont think to set everything equal to 0. Thanks

Bunuel wrote:
emmak wrote:
For integers a, b, and c, if ab = bc, then which of the following must also be true?

A. a = c
B. a^2*b=b*c^2
C. a/c = 1
D. abc > bc
E. a + b + c = 0


\(ab = bc\) --> \(ab-bc=0\) --> \(b(a-c)=0\)--> \(b=0\) or \(a=c\).


A. a = c. If \(b=0\), then this option is not necessarily true.

B. a^2*b=b*c^2 --> \(b(a^2-c^2)=0\) --> \(b(a-c)(a+c)=0\). Now, since \(b=0\) or \(a=c\), then \(b(a-c)(a+c)\) does equal to zero. So, we have that this options must be true.

C. a/c = 1. If \(b=0\), then this option is not necessarily true.

D. abc > bc. If \(b=0\), then this option is not true.

E. a + b + c = 0. If \(b=0\), then this option is not necessarily true (if b=0 then a+c can take any value this option is not necessarily true.).

Answer: B.
Intern
Intern
Joined: 16 Jun 2019
Posts: 2
Own Kudos [?]: 0 [0]
Given Kudos: 0
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
I have the same question

dhlee922 wrote:
i'm still a little confused by the answer choices.

is it because the question stem equates to B=0 OR A=C

so for answer choice A, A doesnt have to equal C because the B equaling 0 will just make the whole expression 0

but then for answer choice B, since B=0 OR A=C, since 1 or the 3 groups in parentheses will be 0, it will make the whole expression 0, therefore B must be true?
Manager
Manager
Joined: 06 May 2019
Posts: 85
Own Kudos [?]: 105 [1]
Given Kudos: 7
Location: India
Concentration: Leadership, Finance
Schools: LBS '22
GMAT 1: 710 Q51 V35
GPA: 4
WE:Information Technology (Computer Software)
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
1
Kudos
@permalink,

Actually this is very good question, it checks your reasoning skills.
Here is solution -

Given : ab = bc , a,b,c are integers,-
let's solve step by step -
ab = bc ---> b(a-c) = 0 ------> either b = 0 or a - c = 0,

hence ,
option (A) a = c must be true ???? lets' check a-c = 0 how we are sure from given information --- because here is no idea about what is value of b ... may be from given information b = 0 and a = 4 , c = 5 , then how a = c must be true ??? hence..here is no clarity...no this option may be true but not must be true. so option(A) is not correct.

before option(B) will check rest options -

Option(C) a/c = 1 must be ?????? ..how we can are sure.. we don't have any idea about value of b..b may be 0 , and maybe a= 4, c= 7....so a/c =1 ..not possible..hence..here are this option is not correct.

Option(D) abc>bc...????? ...if b= 0..then ???...this option is also not correct.

Option(E) --- out of scope.

let's come for option(B)-

here ba^2 =bc^2 -----> b(a-c)(a+c) = 0 ...and form given information either a=c or b=0..hence...if b= 0 or a -c = 0 then satisfy --lhs =rhs...hence this option must be true.

hence option B is correct.

I hope you understand.

If like my solution please give kudos...
Director
Director
Joined: 09 Jan 2020
Posts: 955
Own Kudos [?]: 230 [0]
Given Kudos: 432
Location: United States
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
emmak wrote:
For integers a, b, and c, if ab = bc, then which of the following must also be true?

A. a = c
B. a^2*b=b*c^2
C. a/c = 1
D. abc > bc
E. a + b + c = 0


If \(ab = bc\), then

\(ab - bc = 0\)

\(b(a-c) = 0\)

\(b = 0\) or \(a = c\)

Lets look at the statements:

A. Doesn't have to be true. b could equal 0.

B. \(a^2*b=b*c^2\)

\(a^2*b - c^2*b = 0\)

\(b(a^2 - c^2) = 0\)

\(b(a+c)(a-c) = 0\\
\)
Must be true.

C. Doesn't have to be true. b could equal 0.

D. \(abc > bc\)

\(abc - bc >0\)

\(bc(a-1) > 0\)

Not necessarily true.

E. Cleary wrong.

Answer is B.
Manager
Manager
Joined: 16 Oct 2011
Posts: 170
Own Kudos [?]: 125 [0]
Given Kudos: 545
GMAT 1: 640 Q38 V40
GMAT 2: 650 Q44 V36
GMAT 3: 570 Q31 V38
GMAT 4: 720 Q49 V40
GPA: 3.75
Send PM
For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
emmak wrote:
For integers a, b, and c, if ab = bc, then which of the following must also be true?

A. a = c
B. a^2*b=b*c^2
C. a/c = 1
D. abc > bc
E. a + b + c = 0



ab=bc factors to b(a-c)=0. This means b = 0 or a-c =0 ---> a=c, or both arguments are true.

A. a=c not neccessarilly true if b=0 elim
B. a^2b=bc^2---> a^2b-bc^2=0--> b(a^2-c^2) = 0---> b(a+c)(a-c) = 0---> (a+c)*b*(a-c)=0 since we get a scale multiple of our original argument, this must also be true.

OA is B
User avatar
Non-Human User
Joined: 09 Sep 2013
Posts: 33636
Own Kudos [?]: 839 [0]
Given Kudos: 0
Send PM
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
GMAT Club Bot
Re: For integers a, b, and c, if ab = bc, then which of the foll [#permalink]
Moderator:
Math Expert
93895 posts